Eye tracker, binocular vision and oculomotor balance: exploratory study - Mendanha, Luís (2005)
We have analysed the vision direction with the Eye Tracker System ASL-model 504 of individuals with alterations of oculomotor balance or binocular vision, comparing them with individuals without those kinds of alterations. The sample was composed of 40 individuals, men, and women, with ages between 18 and 23. They were distributed as follows: individuals with normal binocular vision (NBV) in binocular and monocular conditions and with convergence insufficiency (CI). Significant differences were found between the studied groups, pointing out that the absence of binocularity, as the existence of convergence insufficiency, entails clearly a quality loss of the visual pursuit.